2021
DOI: 10.1002/cam4.4454
|View full text |Cite
|
Sign up to set email alerts
|

Levetiracetam as a sensitizer of concurrent chemoradiotherapy in newly diagnosed glioblastoma: An open‐label phase 2 study

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Despite advances in chemotherapy therapy, patients with GBM who have undergone surgery are confronted by drug resistance and tumor recurrence; these factors can lead to immense physical and financial stress. Hwang et al reported the negative results for patients with GBM in their clinical trial for LEV on the survival benefits of patients with GBM in 2022 [ 19 ], which is opposite to their observational study [ 30 ]. However, this study was limited by its single-arm design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite advances in chemotherapy therapy, patients with GBM who have undergone surgery are confronted by drug resistance and tumor recurrence; these factors can lead to immense physical and financial stress. Hwang et al reported the negative results for patients with GBM in their clinical trial for LEV on the survival benefits of patients with GBM in 2022 [ 19 ], which is opposite to their observational study [ 30 ]. However, this study was limited by its single-arm design.…”
Section: Discussionmentioning
confidence: 99%
“…No differences were found in survival as a result of LEV. LEV had no significant side effects or overdose symptoms in the study, even when patients received an increased dose of up to 2000 mg/day and other AEDs as well [ 19 ]. However, the study was limited by a single-arm study design with external and historical control.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of glioma-neuron interactions has now been established, however there are likely multiple mechanisms driving synaptogenesis and non-synaptic peritumoral hyperexcitability. 3941 Whether treatment aimed at reducing neuronal firing impacts the clinical course of disease, as suggested in animal models and some small retrospective cohorts, 5,1215,17 remains uncertain. For example, early glioma-related hyperexcitability in clinical EEG recordings has been associated with decreased overall survival despite treatment with ASMs, 42 while meta-analysis and a large pooled study of contemporary clinical trials for glioblastoma found no associations between the use of valproic acid or levetiracetam and survival outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, post hoc analyses in neuro-oncology cohorts evaluating tumor outcomes associated with ASM exposure have provided conflicting results and have been inherently limited by indication bias. [8][9][10][11][12][13][14][15][16][17][18][19] The selective post-synaptic AMPA-R antagonists, talampanal and perampanel, have demonstrated promising anti-seizure effects, [20][21][22][23][24] although their impact on clinical tumor outcomes remains uncertain. [17][18][19] Furthermore, it is unclear whether targeting glutamatergic signaling provides an advantage over targeting other mechanisms of excessive synaptic activity with first-line broad-spectrum ASMs such as levetiracetam.…”
Section: Introductionmentioning
confidence: 99%
“…Levetiracetam (LEV), a relatively new antiepileptic drug, modulates HDAC levels ultimately silencing MGMT, thus increasing TMZ effectiveness in GCSs [ 224 ]. Retrospective analyses and an open-label phase II study (NCT02815410) seem to evidence that LEV improves GB patients’ PFS and OS [ 225 , 226 ]. So, it is perhaps time to reconsider the results performed in 2016, where a pooled analysis of a large series of cases treated with valproic acid or levetiracetam failed to find an association with patients’ survival [ 227 ].…”
Section: Lessons Learned In the Pathophysiology Of Glioblastomamentioning
confidence: 99%